2009
DOI: 10.1158/1078-0432.ccr-08-2138
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Phosphorylated Mammalian Target of Rapamycin Predicts Lymph Node Metastasis and Prognosis of Chinese Patients with Gastric Cancer

Abstract: Purpose: We determined the expression of mammalian target of rapamycin (mTOR) and its activated form, p-mTOR, in Chinese patients with gastric cancer and its clinical effects and underlying mechanisms. Experimental Design: Tissue microarray blocks containing gastric cancer tissue and matched noncancer gastric tissue specimens obtained from 1,072 patients were constructed. Expression of total mTOR and p-mTOR in these specimens was analyzed using immunohistochemical studies and confirmed by Wester… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
94
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 42 publications
7
94
0
2
Order By: Relevance
“…It has been suggested that the expression of p-P70S6K and p-mTOR is associated with various clinicopathological variables in certain non-colorectal tumors. For example, Yu et al reported that overexpression of the mTOR protein was significantly associated with tumor differentiation, T1 and 2 tumors and stage I-III disease, whereas p-mTOR overexpression was significantly associated with the occurrence of lymph node metastasis and all stages of disease (26). Wang et al reported that the expression of mTOR and p-mTOR may play an important role in colorectal carcinogenesis, with an association between the expression of mTOR and the degree of differentiation, invasiveness and metastatic ability of the lesions (27).…”
Section: A B Discussionmentioning
confidence: 99%
“…It has been suggested that the expression of p-P70S6K and p-mTOR is associated with various clinicopathological variables in certain non-colorectal tumors. For example, Yu et al reported that overexpression of the mTOR protein was significantly associated with tumor differentiation, T1 and 2 tumors and stage I-III disease, whereas p-mTOR overexpression was significantly associated with the occurrence of lymph node metastasis and all stages of disease (26). Wang et al reported that the expression of mTOR and p-mTOR may play an important role in colorectal carcinogenesis, with an association between the expression of mTOR and the degree of differentiation, invasiveness and metastatic ability of the lesions (27).…”
Section: A B Discussionmentioning
confidence: 99%
“…Patients testing positive for the abnormal expression of the PI3K/AKT/mTOR pathway were more likely to be in the late stages of gastric cancer with a lower survival rate. [4][5][6][7] Several drugs targeting PI3K/AKT/mTOR pathways are currently in clinical trials for gastric cancer, including PI3K inhibitor (LY294002, MK2206), AKT inhibitor (MLN1117), and mTOR inhibitor (everolimus). [8][9][10][11] PI3K inhibitor and AKT inhibitor monotherapy showed promising effects in Phases I-II, while mTOR inhibitor failed to improve survival in the GRANITE-1 Stage III trial for advanced gastric cancer.…”
mentioning
confidence: 99%
“…A score 4 was considered to be positive. 4,5,7 statistical analysis Statistical Package for the Social Sciences (SPSS) version 16.0 (SPSS Inc., Chicago, IL, USA) was used for the statistical analysis. The correlation between PI3K, p-AKT, and p-mTOR expression and patient clinicopathologic factors was analyzed using the χ 2 test.…”
mentioning
confidence: 99%
“…It has been reported that mTOR is a powerful oncoprotein overexpressed in numerous types of cancer, including hepatocellular carcinoma (22), lung cancer (23), esophageal squamous cell carcinoma (24) and breast cancer (25,26). Furthermore, patients with breast cancer and mTOR overexpression had a risk of recurrence 3 times greater than that of patients without mTOR overexpression (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with breast cancer and mTOR overexpression had a risk of recurrence 3 times greater than that of patients without mTOR overexpression (25,27). The mTOR inhibitor everolimus has demonstrated promising clinical efficacy in a phase III randomized and double-blind trial in patients with metastatic renal cell cancer (28).…”
Section: Discussionmentioning
confidence: 99%